Used engine oil as alternate binder for buildings - A comparative study - Nadeem, H. (ICE Publishing, 2017)
At present, global warming and climate change are the major challenges of foremost significance that substantially influence the earth's environment. The construction sector, especially buildings, is one of the largest sources of greenhouse gas emissions. Conventional building materials such as clay bricks and cement are considered as environmentally unfriendly due to enormous emissions during their production. This paper investigates the utilisation of used engine oil (UEO) as an alternative to the usual cementitious binders. Prototypes were produced from UEO to optimise the compositions and conditions of the process and tested for compressive and flexural strength, permeability and water absorption, respectively, following the ASTM standards. Furthermore, environmental and weathering aspects were also demonstrated to ensure the feasibility of the product. Samples constituting 5 by weight UEO have shown significant results for flexural stress, compressive strength and water absorption and also passed the permeability test. Moreover, 5 of UEO samples have negligible effect in strength for accelerated weathering conditions as demonstrated by the ultraviolet test. Conclusively, UEO can be used as a replacement to conventional binding materials such as a clay bricks and cement. Sustainable development and waste management are the hallmarks of this research.